HUBUNGAN PEMBERIAN HUKUMAN TERHADAP KEDISIPLINAN SISWA KELAS III SDN PORIS PELAWAD 6 - Siti Selfiyana; Mawardi; Moh. Zamroni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the results of the analysis described above, it was found that the results of the independent variable (X) giving punishment had a significant relationship with the dependent variable (Y) Discipline of Class III students at SDN Poris Pelawad 6. This was shown by the regression equation Y = 10,963 + 0.188 X. This equation is in accordance with simple linear regression, namely Y = α ≠ ꞵ variable Y, in other words accepting H1, namely that there is a relationship between giving punishment to the discipline of Class III students at SDN Poris Pelawad 6, and rejecting H0, namely that there is no relationship between giving punishment to the discipline of class III students at SDN Poris Pelawad 6.